An investigation on the thixotropic parameters and mechanical properties of loess - Wei, Le; Dang, Faning; Ding, Jiulong (Frontiers in Earth Science, 2023)
The analysis of thixotropic mechanical properties of loess has a significant influence on the calculation of the strength of compacted loess foundation. In order to distinguish the consolidation growth strength of loess from the thixotropic strength, a resting thixotropic instrument is developed. The proposed device is capable of maintaining a constant volume pressure. To attain the goals, after selecting the representative Xi’an loess, the samples were pressed by the resting thixotropic instrument under constant volume pressure. Eight resting ages were also set. Moreover, the thixotropic mechanical properties of loess soil were studied at 6 months resting ages through uniaxial compression without lateral limit and triaxial CU test. The thixotropic triaxial shear strength ratio Jt, thixotropic triaxial shear strength recovery ratio Kt and thixotropic cohesion recovery ratio Lt were defined, the mechanical properties of which were investigated under different stress states. The obtained results demonstrated the obvious thixotropy of Xi’an loess, the strength of which was found to increase with an increase in the resting age. This is while, an increase in the resting age was observed to decrease the its growth rate. Moreover, the unconfined thixotropic strength was found to increase by 1.75 times after resting for 160d, which corroborates the influence of thixotropic strength in designing the foundation bearing capacity of loess. Furthermore, the recovery ratio of unconfined thixotropic strength and the growth ratio of eccentric stress strength were found to be 0.187 and 0.115, respectively. In addition, the thixotropic triaxial shear strength ratio Jt, the recovery ratio of thixotropic triaxial shear strength ratio Kt, and the recovery ratio of thixotropic cohesion ratio Lt were observed to be 0.15, 0.527, and 0.5, respectively. The obtained results suggest the resting age of 40 days to be used as the inflection point for the recovery of thixotropic strength such as uniaxial compressive strength, peak deviator stress, shear strength and cohesion of loess. Despite the insignificant variation range of the friction Angle in the resting process, the contribution ratio of friction force in increasing the shear strength was also found to be much greater than that of the cohesion.